SOME SEQUENCE SPACES AND MATRIX TRANSFORMATIONS IN MULTIPLICATIVE SENSE - Cakmak, Ahmet Faruk; Basar, Feyzi (INST APPLIED MATHEMATICS, 2015)
In this paper, based on multiplicative calculus matrix transformations in sequence spaces are studied and characterized. Also, we give a brief introduction to *- summability based on multiplicative type addition (or just multiplication) and define the multiplicative dual *-summability methods using *-Stieltjes integral and multiplicative differentiation under the *-integral sign.
Keywords: multiplicative calculus; multiplicative differentiation; multiplicative integral; CALCULUS; Mathematics